당뇨병 및 말기신부전을 동반한 당뇨 환자의 발목 골절 후 발생한 샤르코 관절병증 치료: 증례 보고 - 최길원; 임정원; 박승환; Gil-Won Choi; Jung-Won Lim; Seung-Hwan Park (대한족부족관절학회지, 2025)
Charcot neuroarthropathy (CN), also known as Charcot arthropathy, is a complex, progressive disorder primarily affecting the foot and ankle. This case report describes a multifaceted management strategy for a 54-year-old male with diabetes mellitus, end-stage renal disease, and presumed underlying Charcot arthropathy who experienced a traumatic ankle fracture. The initial surgical plans were delayed because of systemic infection indicators, including elevated C-reactive protein levels and high fever. The patient underwent multiple surgical interventions and faced challenges, including metal failure, implant-associated infection, and tibiotalar joint dislocation. A multidisciplinary approach involving orthopedic surgeons, nephrologists, and endocrinologists was crucial for managing the case effectively. In particular, the patient declined a below-knee amputation and opted for comprehensive surgical intervention, resulting in improved functionality at the latest follow-up. This case highlights the complexities of managing CN in patients with multiple comorbidities and emphasizes the need for a nuanced, patient-centered approach.